The effect of subject-specific teacher qualifications on student science achievement - Vera Freundl; Pietro Sancassani (CESifo GmbH, 2023)
What makes a good teacher? This is one of the central questions in the economics of education. General teacher qualifications, such as education level or advanced degrees, tend to be poor predictors of teacher quality. Instead, some studies have shown that subject-specific qualifications predict teacher quality better. However, the vast majority of such studies are based on data from the United States. It is therefore unclear to what extent the findings can be generalized to other nations, as teacher education programs vary widely across countries. The lack of international evidence is particularly problematic for developing economies, which would arguably benefit most from improving student achievement.
Keywords: 330; Lehrkräfte; Qualifikation; MINT-Fächer; Wirkungsanalyse; Schüler; Bildungsniveau; Welt